2020
DOI: 10.1111/1759-7714.13790
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung disease associated with capmatinib therapy in a patient with non‐small cell lung cancer harboring a skipping mutation of MET exon 14

Abstract: Capmatinib is a MET tyrosine kinase inhibitor (TKI) that has recently been approved for the treatment of advanced non–small cell lung cancer (NSCLC) positive for skipping mutations of MET exon 14 (METex14). Drug‐induced interstitial lung disease (ILD) is a relatively rare, but potentially serious, side effect of TKIs administered for lung cancer treatment. Here we report a case of capmatinib‐induced ILD in a patient with NSCLC harboring a METex14 skipping mutation. Capmatinib should be immediately discontinued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Although MET TKI-induced ILDs have been reported, 2 , 3 , 5 whether MET TKIs can be rechallenged after MET TKI-induced ILDs remains unknown. In this case, we decided to switch from capmatinib to tepotinib after capmatinib-induced ILD because she still had a chance to get a survival benefit from the MET TKIs after a series of multiple anticancer regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Although MET TKI-induced ILDs have been reported, 2 , 3 , 5 whether MET TKIs can be rechallenged after MET TKI-induced ILDs remains unknown. In this case, we decided to switch from capmatinib to tepotinib after capmatinib-induced ILD because she still had a chance to get a survival benefit from the MET TKIs after a series of multiple anticancer regimens.…”
Section: Discussionmentioning
confidence: 99%
“…In July and August 2022, the patient underwent a radiological re-evaluation for cancer staging using CT and 18 F fluorodeoxyglucose (FDG) positron emission tomography (PET). The IMA lesions had modestly extended into the up-per and middle lobes over the past year, with marginal lymph node enlargement observed on CT (Fig.…”
Section: Casementioning
confidence: 99%
“… 81 , 82 Rare cases of severe respiratory adverse events (AEs) (including pneumonitis and interstitial lung disease) have been reported with some ALK, EGFR, and MET inhibitors, which could limit the use of these therapies before surgical resection. 83 , 84 Other reported rare toxicities that may impact surgery include the following: cardiotoxicity (osimertinib), 85 , 86 bradycardia (alectinib and crizotinib), 87 , 88 thrombocytopenia (osimertinib), 89 fever (dabrafenib plus trametinib), 90 hepatotoxicity (sotorasib), 91 and CNS toxicity (lorlatinib). 92 Preliminary results from the ALK -positive cohort of the NAUTIKA1 study demonstrated that neoadjuvant alectinib was well tolerated in patients with resectable NSCLC, and to date, all patients have undergone surgery without delays or major complications.…”
Section: Safety Considerations Of Neoadjuvant Ttsmentioning
confidence: 99%